Danish Sixties Avant-Garde and American Minimal Art - Ipsen, Max (Nordlit, 2007)
Denmark is peripheral in the history of minimalism in the arts. In an international perspective Danish artists made almost no contributions to minimalism, according to art historians. But the fact is that Danish artists made minimalist works of art, and they did it very early.Art historians tend to describe minimal art as an entirely American phenomenon. America is the centre, Europe the periphery that lagged behind the centre, imitating American art. I will try to query this view with examples from Danish minimalism. I will discuss minimalist tendencies in Danish art and literature in the 1960s, and I will examine whether one can claim that Danish artists were influenced by American minimal art.
Keywords: Danish minimalism; Danish art and literature; 1960s